Using Extreme Pedagogy to Enhance Entrepreneurship Education. (7th July 2023) - Silberman, Dave; Aguinis, Herman; Carpenter, Rob E.
We address the ongoing concern that entrepreneurship education (EE) is not preparing students sufficiently well for jobs in the 21 st -century. We argue that many criticisms leveled against EE for not effectively addressing the entrepreneurial skills gap are due in part to EE's emphasis on the roles of specific stakeholder groups separately (i.e., universities and their leaders, instructors, students, potential employers) rather than a shared focus on developing valuable graduates. Stated differently, there are competing and conflicting "ownerships" over the entrepreneurial skills gap. We enhance current pedagogical methods by offering a learning innovation called extreme pedagogy. Extreme pedagogy takes place when all stakeholders have a collective intention and ownership in producing graduates with relevant entrepreneurial skills. We describe extreme pedagogy's conceptual foundation based on psychological ownership theory, the effective of use of extreme ownership in military contexts, and the role of universities and their leaders, instructors, students, and potential employers in the implementation of extreme pedagogy. We then summarize themes from a workshop involving entrepreneurial leaders across industries on EE challenges and the role of extreme pedagogy in addressing them. We close by describing anticipated benefits of extreme pedagogy for all EE stakeholders.